Implementation of Diniyah Education in Strengthening Islamic Religious Education at SDN Gondangmanis - Fu’in, Hilwa Saida; Mufidah, Luluk Indarinul; Lailaturrosidah, Azah; Khatib, Ach.; Hisyam, Mohammad (STAI Miftahul Ula Nganjuk, 2024)
The provision of Islamic education from an early age is crucial in reinforcing Islamic religious education. It involves intentional guidance given to children in their physical and spiritual development until they reach maturity, with the goal of assisting them in achieving adulthood. This study employs a case study methodology with a qualitative approach, and data were collected through qualitative methods, including observation, interviews, and documentation. The findings of this study conclude that the implementation of diniyah education has been effective, adhering to the guidelines and procedures established for diniyah education. The implementation of madrasah diniyah in strengthening the Islamic Religious Education curriculum includes formulating the main objectives of diniyah education, developing teaching materials, selecting competent teachers in Islamic education, employing enjoyable teaching methods and strategies, and conducting evaluations. The results of diniyah education implementation include the Cognitive Domain: students have begun to write Arabic correctly and accurately. The Affective Domain: observable through students’ increasingly polite and responsible behavior. Finally, the Psychomotor Domain has also shown positive outcomes